Time-of-day variation on performance measures in repeated-sprint tests: a systematic review - Pullinger, S. A.; Cocking, S.; Robertson, C. M.; Tod, D.; Doran, D. A.; Burniston, J. G.; Varamenti, E.; Edwards, B. J. (Chronobiology International, 2020)
The lack of standardization of methods and procedures have hindered agreement in the literature related to time-of-day effects on repeated sprint performance and needs clarification. Therefore, the aim of the present study was to investigate and systematically review the evidence relating to time-of-day based on performance measures in repeated-sprints.